A synthetic promoter for multi-stage expression to probe complementary functions of Plasmodium adhesins - Klug, Dennis; Kehrer, Jessica; Frischknecht, Friedrich; Singer, Mirko (Journal of cell science, 2018)
Gene expression of malaria parasites is mediated by the apicomplexan Apetala2 (ApiAP2) transcription factor family. Different ApiAP2s control gene expression at distinct stages in the complex life cycle of the parasite, ensuring timely expression of stage-specific genes. ApiAP2s recognize short cis-regulatory elements that are enriched in the upstream/promoter region of their target genes. This should, in principle, allow the generation of ‘synthetic’ promoters that drive gene expression at desired stages of the Plasmodium life cycle. Here we test this concept by combining cis-regulatory elements of two genes expressed successively within the mosquito part of the life cycle.